Transition Metal-Catalyzed Carbon Upcycling - 정연주 (The Graduate School, Ajou University, 2022)
Modern society is depleting energy due to the limited amount of energy sources and increased energy consumption. The combustion of fossil fuels generates pollutants, and global warming is becoming severe due to carbon dioxide (CO2) emissions. To solve environmental problems, carbon upcycling, which can reduce CO2 through recycling of emitted CO2, is promising. Carbon upcycling refers to a technology that converts by-product gas from industry or carbon sources from organic waste resources into high value-added products. It can be categorized into carbon capture (CC), which captures CO2 emitted from industry, carbon storage (CS), which is then stored, and carbon utilization (CU) technology that converts them into high value-added products. In this study, we focused on carbon utilization process development. We developed transition metal complexes to produce valuable products through the simultaneous conversion of CO2 and glycerol. To develop suitable catalysts, iridium complexes were designed and synthesized using ligands of various structures. Especially, N-heterocyclic carbene (NHC), which has strong σ donor and weak π acceptor ability, was used to enhance the stability and efficiency of the catalyst. Transition metal-catalyzed chemical transformation can add value to waste. In this study, the dehydrogenation of glycerol and the simultaneous conversion of glycerol and CO2 were performed using the Ir-NHCs complexes. Glycerol is used as a sustainable hydrogen donor. Development of the chemical transformation of glycerol would provide environmental benefits in chemical industries. Hydrogen gas can be produced through dehydrogenation. Hydrogen energy, obtained only with water as a by-product during combustion, is spotlighted as an eco-friendly next-generation energy source. The conventional hydrogen production process generates CO2, and hydrogen production through hydrolysis using a photocatalyst is not commercially available. Therefore, transition metal-catalyzed large-scale production of hydrogen from glycerol is a very attractive process. In addition, lactic acid (LA), a product of dehydrogenation of glycerol, has the potential to be applied to various industries, such as being used as a monomer for bio-based polymer, poly(lactic acid) (PLA) Through this study, structural differences between monometallic and bimetallic were confirmed. In addition, hydrogen and lactic acid were produced with very high catalytic efficiency. Transition metal-catalyzed transfer hydrogenation (TH) is a reaction in which a hydrogen atom is transferred from a donor to an acceptor. In this study, CO2 was used as the H-acceptor. Direct hydrogenation of CO2 uses hydrogen gas, which is explosive. However, glycerol, a liquid organic hydrogen carrier (LOHC), is a safer hydrogen source. Also, TH is an atom economic reaction that can minimize by-products by using an equivalent amount of a base. We synthesized iridium complexes using two types of ligands: (a) Ir complexes with bidentate bisNHCs, and (b) mono- and bi-metallic Ir complexes with linear trisNHCs. Complexes showed very high catalytic efficiency in the TH of CO2 and glycerol. Miscellaneously, transition metal-catalyzed borrowing hydrogen reaction, such as direct conversion of amines to alcohols, was conducted. The dehydrogenation of amines is slower than the dehydrogenation of alcohols, and transamination in which amines are added to imine obtained as an intermediate may proceed. Therefore, the direct conversion of amines to alcohols is challenging, and the studies are rarely reported. We developed the Ir(III)-(NHCs) complexes and successfully carried out the reaction. Glycerol was used together as a hydrogen source to form Metal-H species rapidly, which allows the conversion to alcohol to dominate. Herein, we report the synthesis of new Ir(I)- and Ir(III)-NHCs complexes with various structures. Dehydrogenation using glycerol, TH of glycerol and CO2, and direct conversion of amine to alcohol using glycerol were performed using them. As a result, they are very efficient to desired reactions. Through this study, the effect of reducing CO2 and producing high value-added products can be expected. Also, to develop a method for synthesizing various organic compounds through chemical conversion can be expected.
학위논문(박사)--아주대학교 일반대학원 :에너지시스템학과,2022. 2
Keywords: Carbon dioxide; Carbon upcycling; Glycerol; Iridium; Trasnfer hydrognation